A taste for exotic food: Neotropical land planarians feeding on an invasive flatworm - Piter K. Boll; Ilana Rossi; Silvana V. Amaral; Ana Leal-Zanchet (PeerJ, 2015)
Invasive species establish successfully in new habitats especially due to their ability to include new species in their diet and due to the freedom from natural enemies. However, native species may also adapt to the use of new elements in their ecosystem. The planarian Endeavouria septemlineata, first recorded in Hawaii, was later found in Brazil. Recently, we found it in human-disturbed areas in southern Brazil and here we investigate its interactions with other invertebrates both in the field and in the laboratory. We observed the species in the field during collecting activities and hence maintained some specimens alive in small terraria in the laboratory, where we offered different invertebrate species as potential prey and also put them in contact with native land planarians in order to examine their interaction. Both in the field and in the laboratory, E. septemlineata showed a gregarious behavior and was found feeding on woodlice, millipedes, earwigs and gastropods. In the laboratory, specimens often did not attack live prey, but immediately approached dead specimens, indicating a scavenging behavior. In an experiment using the slug Deroceras laeve and the woodlouse Atlantoscia floridana, there was a higher consumption of dead specimens of woodlice and slugs compared to live specimens, as well as a higher consumption of dead woodlice over dead slugs. Four native land planarians of the genus Obama and one of the genus Paraba attacked and consumed E. septemlineata, which, after the beginning of the attack, tried to escape by tumbling or using autotomy. As a scavenger, E. septemlineata would have no impact on the populations of species used as food, but could possibly exclude native scavengers by competition. On the other hand, its consumption by native land planarians may control its spread and thus reduce its impact on the ecosystem.